Napoli vicereale e le altre corti spagnole in Italia - Antonelli, Attilio; Chiantore, Francesca; Mazzola, Elena (Clio. Essays in History, Archaeology and Art History, 2023)
This book contains the papers of the conference Napoli e le corti vicereali nell'età spagnola, held on 14th May 2021 by remote, to celebrate the completion of the series I cerimoniali della corte di Napoli, edited over the last ten years by Attilio Antonelli and sponsored by the Soprintendenza Archeologia, Belle Arti e Paesaggio for the City of Naples.The essays analyse the Spanish courts present in Italy between Naples, Milan, Cagliari and Palermo. Particular attention is devoted to festivals, ceremonies, performances and sacred and musical events. The book, with an introduction by Giovanni Muto, contains essays by Carlos José Hernando Sánchez, Lina Scalisi, Nicoletta Bazzano, Cinzia Cremonini, Verónica Gallego Manzanares and Ida Mauro, Ángel Rivas Albaladejo, Elisa Novi Chavarria, and Dinko Fabris.